Online Consumer Product Purchasing Behavior Post Covid-19 - Sungkawati, Endang; Anugerah, Roy; Almira Mardhiyah, Marsha (International Journal of Science, Technology & Management, 2023)
The rapid development of technology in the world has led to changes in culture and daily habits, making internet access easier. The internet has brought great changes to all aspects of life, particularly within the development of the business and marketing world, in line with the increasing number of internet users causing many companies to change the structure of people's shopping to be made online. This study aims to determine the effect of price, trust, convenience and security of online internet purchasing decisions both partially and simultaneously. This research was conducted using quantitative research methods. The analysis technique used in this research is multiple linear regression. The results shows partially that the convenience variable had a positive and significant effect on online purchasing decisions, while the price, trust, and security variables had either no or little significance on online purchasing decisions. Simultaneously, it is known that the variables of price, trust, convenience, and security has a positive and significant effect on online purchasing decisions.